Postharvest physiological and biochemical characteristics of Syzygium samarangense fruits / Maryam Tehrani - Tehrani, Maryam (2012)
Little data is available in the scientific literature on postharvest changes taking place in three varieties of Syzygium samarangense fruits, an increasingly popular fruit in the Asian region. In this study, the postharvest physico-chemical and mechanical properties of three varieties of Syzygium samarangense (red, pink and deep red) namely, fruit color, weight loss, pulp firmness, total soluble solids, pH, titratable acidity, total sugar, total starch and total protein were determined during the postharvest storage period under ambient conditions of Syzygium samarangense fruits. It was observed that weight loss, total soluble solids (TSS), pH, total sugar and total protein of the jambu air fruits increased significantly (p < 0.05) with time whilst pulp firmness, total starch and the color index of the fruits decreased. Analysis of the antioxidant activity, determined in the methanol extracts of the jambu fruit extracts over a period of 9 days after harvesting, using the DPPH (2,2-diphenyl-1-picrylhydrazyl) and the ABTS (2,2 azino-bis-(3-ethylbenzthiazoline-6-suphonic acid) methods, showed that the antioxidant activity increased gradually during post harvest ripening. The total phenol content determined by the Folin-Ciocalteau method revealed a high concentration of phenol content in the jambu fruits, with values around 372.62 ± 69.64, 188.59 ± 24.22 and 254.27 ± 78.20 mg gallic acid equivalent (GAE) / 100g fresh fruit in red, pink and deep red S. samarangense, respectively. Similarly, the flavonoid content measured spectrophotometrically, using the aluminum chloride colorimetric assay, also showed an increasing trend over the same period. The results were expressed as mg of ascorbic acid equivalent (AAE), GAE and catechin equivalent (CE) per 100g of sample. The activity of L-phenylalanine ammonia-lyase (PAL), was also studied in the jambu fruits. PAL activity increased significantly (p < 0.05) throughout the ripening process. These results represent new data on postharvest changes occurring in Syzygium samarangense fruits and show that this increasingly popular fruit has great potential for future development in the agriculture sector.